Politics of Identity in Small Plural Societies - Wilson, S. author. aut Link
XIII, 219 p.
Keywords: In small plural societies, cultural differences can be exaggerated, exploited and intensified during political contests. The survival of these societies as democracies - or even at all - hangs in the balance.